Complications of transperineal template‐guided prostate biopsy: A single centre experience in 109 cases. Issue 3 (August 2017) - Cronin, Thomas; Neill, Lorna; Nelson, Johanne; Stewart, Rachel; Sangster, Philippa; Khoubehi, Bijan
Abstract : Aim: The aim of the current study was to present the complications for patients undergoing a template‐guided transperineal prostate biopsy (TPB) at a single centre. Patients and Methods: Data from 109 consecutive patients undergoing TPB over a 1‐year period were analysed. TPB was performed as a day‐case procedure under general anaesthesia. At the time of induction, patients received a single dose of coamoxiclav as the prophylactic antibiotic. This is in contrast to transrectal ultrasound‐guided prostate biopsy, which frequently uses multiple antibiotics and for an extended period. Results: The mean age of the studied patients was 65 years, the mean prostate‐specific antigen value was 10.45 ng/L and the mean prostate volume was 61.5 mL. Eight patients (7.2 per cent) were identified as having experienced morbidity due to TPB. Three patients (2.8 per cent) developed urinary retention in the immediate postoperative period. Five patients (4.6 per cent) attended the emergency department at the institution with a presentation related to the procedure; one due to pain, one due to haematuria and three from urinary retention (despite having passed urine after the operation). Conclusion: There was a low incidence of complications following TPB at this institution. Specifically, there were no cases of infection related to the procedure. The most common morbidity resulting from TPB was urinary retention. Future research should be targeted towards investigating ways to minimize the risk of urinary retention following TPB.